Karakteristik Dan Tingkat Konsumsi Vitamin B6, B12, Dan Asam Folat Pada Pasien Stroke Rawat Inap - Novita Rahayu Lestari; Suhaema Suhaema; Ni Ketut Sulendri; Fifi Lutfiah (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background. Stroke is a cerebrovascular disease (cerebral blood vessel) that is characterized by impaired brain function due to damage or death of brain tissue due to reduced or blocked blood flow and oxygen to the brain. Stroke is influenced by several factors, namely risk factors that cannot be controlled, and risk factors that can be controlled. Risk factors that cannot be controlled include age, gender, smoking habits, and risk factors that can be controlled consisting of a history of hypertension, a history of diabetes mellitus, and hypercholesterolemia. Todetermine the description of the level of consumption of vitamins B6, B12, and folic acid in Stroke Patients Hospitalized in the BRSUD of Tabanan Regency. Research Methods. The type of research conducted is Descriptive Observational. Research Result. Based on age, as many as 5 people (71%). ≥ 55 years old. The sex of the most subjects having strokes was women with 4 people (57%). Distribution of the type of work of the subject is entrepreneur as many as 4 people (57%), civil servants 1 person (14%) and not working as many as 2 people (29%). Nutritional status of 1 person (14%) malnutrition, 1 person (14%) overweight, and 5 people (72%) good nutrition. Subjects with a history of hypertension were 6 people (86%), and those with a history of hypercholesterolemia as many as 2 people (29%). Subjects who had smoking habits were 1 person (14%). The level of consumption of Vitamin B6, B12, and folic acid in stroke patients, it is known that all subjects have a low consumption level (<80%) with details of vitamin B6 (4.50%), B12 (0.29%), Folic Acid (20, 0%). Conclusion. From this study all patients who suffered strokes consumed less vitamin B6, B12, and folic acid.